Komunikasi Pengurus Masjid Dalam Menajemen Masjid Baburahmah Jorong Tiakar Nagari Guguak VIII Koto Kabupaten 50 Kota - Muhammad Isra; Penmardianto Penmardianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research is motivated by the function of communication in a mosque management which is very important in managing mosque management. In the management of the mosque, of course, there are problems that arise both within the administrators and the relationship between the congregation and the mosque's management. Given the importance of administrator communication in mosque management to achieve mosque prosperity because administrators must be able to manage mosques. The purpose of this research is to find out how the mosque management communicates in the management of the mosque in the mosque. This study used a qualitative research method by collecting data using interviews, observation and documentation on the management of the Baburahmah mosque. The data collection technique that the authors did was interview, observation and documentation with the management of the Baburahmah mosque and the congregation of the Baburahmah Jorong Tiakar mosque. The data analysis technique that the writer uses is the presentation of data and drawing conclusions. From the results of the study it can be concluded that in mosque management there are two types of management, namely Idarah Binail Maaddiy (physical management) and Idarah Bina Ar-Ruhi (function of the mosque). In the communication of mosque administrators for the management of the Baburah Jorong Tiakar mosque, the function of communication here is very important in carrying out the management of the Baburahmah mosque. From Iarah Binail Maaddiy (physical management) there are three discussions, namely the communication of mosque administrators in creating a large and beautiful mosque, the communication of mosque administrators in creating a clean and healthy mosque and the communication of mosque administrators in secretarial management and administration. From Idah Bina Ar-Ruhi (Functions of the Mosque) there are 2 points, namely: the communication of the mosque management in carrying out the function of the mosque as a place of worship and communicating the mosque as a center for religious education.